The Role of Body-Worn Cameras in Shaping the Public Image and Credibility of the Philippine National Police - Zarzoso, Ringo C.; Zarzoso, Tejanne Q; Tumang, Bryan John D (Future Science / FSH-PH Publications, 2025)
This study examined The Role of Body-Worn Cameras (BWCs) in Shaping the Public Image and Credibility of the Philippine National Police (PNP), focusing on their impact on transparency, accountability, public trust, professionalism, and integrity. Conducted in Quezon City under Police Station 7, the study employed a quantitative research design involving 524 respondents—125 police officers and 399 community members selected using Slovin’s formula. Data were collected through validated survey questionnaires administered both in-person and online during the first quarter of 2025. Findings revealed that respondents strongly agreed that BWCs enhanced transparency (????=3.65), accountability (????=3.60), public trust (????=3.59), professionalism (????=3.55), and integrity (????=3.55) within the PNP. The results indicated that BWCs promoted ethical conduct, reduced misconduct, and strengthened public confidence in law enforcement. However, challenges such as limited funding, inadequate training, and data management issues hindered optimal implementation. Despite these barriers, 91% of respondents expressed strong support for the continued use of BWCs in all police operations. A statistically significant difference (p = 0.008) was identified between police officers’ and community members’ perceptions, indicating that their differing roles and experiences shaped how they viewed BWC effectiveness. Overall, the study affirmed that body-worn cameras are critical tools for strengthening the PNP’s transparency, credibility, and institutional integrity.